2018
DOI: 10.1016/j.chest.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Sarcoidosis in World Trade Center-Exposed Firefighters

Abstract: Extrathoracic disease was more prevalent in WTC-related sarcoidosis than reported for patients with sarcoidosis without WTC exposure or for other exposure-related granulomatous diseases (beryllium disease and hypersensitivity pneumonitis). Cardiac involvement would have been missed if evaluation stopped after ECG, 48-h recordings, and echocardiogram. Our results also support the need for advanced cardiac screening in asymptomatic patients with strenuous, stressful, public safety occupations, given the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 27 publications
4
45
0
1
Order By: Relevance
“…An association between the HLA-DQB1*0601 allele and cardiac sarcoidosis was also identified in the Japanese cohort [35]. Interestingly, it is well-known that exposure to mineral and nanoparticles (NNPs) during the NYC World Trade Center disaster in September 2001 has been a predisposing factor to "sarcoidosis-like" granulomatous pulmonary disease among New York Fire Department rescue workers [36]. Even in this highly environmental inducing context, it was recently shown that more that seventeen novel HLA alleles were associated with an increased risk of sarcoidosis in exposed individuals, with OR values varying from 1.66 (HLA-DPA1/HLA-DPB1) to 5.21 (HLA-DRB1) [37].…”
Section: Contribution Of Gwas To Understanding Immunogenetics Of Sarcmentioning
confidence: 90%
“…An association between the HLA-DQB1*0601 allele and cardiac sarcoidosis was also identified in the Japanese cohort [35]. Interestingly, it is well-known that exposure to mineral and nanoparticles (NNPs) during the NYC World Trade Center disaster in September 2001 has been a predisposing factor to "sarcoidosis-like" granulomatous pulmonary disease among New York Fire Department rescue workers [36]. Even in this highly environmental inducing context, it was recently shown that more that seventeen novel HLA alleles were associated with an increased risk of sarcoidosis in exposed individuals, with OR values varying from 1.66 (HLA-DPA1/HLA-DPB1) to 5.21 (HLA-DRB1) [37].…”
Section: Contribution Of Gwas To Understanding Immunogenetics Of Sarcmentioning
confidence: 90%
“…Asymptomatic sarcoidosis may be identified in respiratory surveillance programmes and its early radiological stages can be very difficult to distinguish from CWP or silicosis. There is mounting evidence suggesting a relationship between sarcoidosis and occupational and environmental exposures [27,28], supported by epidemiological studies [29]. Sarcoidosis likely arises from several triggers, with underlying predisposing factors.…”
Section: Other Interstitial Lung Diseasesmentioning
confidence: 99%
“…Because of the extremely high sensitivity and specificity of cardiac MRI for the diagnosis of cardiac sarcoidosis, some have advocated incorporating this "diagnostic test" into the screening algorithm for cardiac sarcoidosis. 57,67 Although the cardiac MRI may be an unattractive screening test for cardiac sarcoidosis on the basis of its exorbitant cost, diagnostic tests such as the cardiac MRI as well as the cardiac PET may be useful not only to diagnose cardiac sarcoidosis but also to provide prognostic information concerning the likelihood of future adverse events. 68,69 Another analysis of a Polish sarcoidosis cohort developed a point system to predict the likelihood of cardiac sarcoidosis.…”
Section: Heartmentioning
confidence: 99%